Transition to first marriage in Thailand: cohort and educational changes - Dommaraju, Premchand (2023)
This paper documents the changes in first marriage in Thailand over a three-decade period. Thailand provides a unique context to examine marriage changes with rapid educational changes, gender egalitarian structures, historically low rates of early marriage and acceptance of non-marriage. The paper focuses on the changes in marriage across birth cohorts and for different educational groups. Data from three rounds of nationally representative Multiple Indicator Cluster Surveys were analysed using discrete-time survival models. Findings reveal a complex pattern of convergence and stability in marriage patterns. Women delayed entering marriage and this change was primarily driven by compositional factors. Education, as expected, had a negative effect on marriage entry. But the effect of education has changed over time. For the two lowest educational groups, there has been a convergence of trends in marriage. However, for women with higher education, marriage patterns diverged from the other educational groups. Though timing of marriage changed, the proportion of higher educated women marrying has remained remarkably stable. The findings reveal the different pathways and implications of educational changes on marriage patterns.